TRPA5, an Ankyrin Subfamily Insect TRP Channel, is Expressed in Antennae of Cydia pomonella (Lepidoptera: Tortricidae) in Multiple Splice Variants. Issue 1 (25th August 2016) - Cattaneo, Alberto Maria; Bengtsson, Jonas Martin; Montagné, Nicolas; Jacquin-Joly, Emmanuelle; Rota-Stabelli, Omar; Salvagnin, Umberto; Bassoli, Angela; Witzgall, Peter; Anfora, Gianfranco
Abstract: Transient receptor potential (TRP) channels are an ancient family of cation channels, working as metabotropic triggers, which respond to physical and chemical environmental cues. Perception of chemical signals mediate reproductive behaviors and is therefore an important target for sustainable management tactics against the codling moth Cydia pomonella L. (Lepidoptera: Tortricidae). However, olfactory behavior strongly depends on diel periodicity and correlation of chemical with physical cues, like temperature, and physical cues thus essentially contribute to the generation of behavioral response. From an antennal transcriptome generated by next generation sequencing, we characterized five candidate TRPs in the codling moth. The coding DNA sequence of one of these was extended to full length, and phylogenetic investigation revealed it to be orthologous of the TRPA5 genes, reported in several insect genomes as members of the insect TRPA group with unknown function but closely related to the thermal sensor pyrexia . Reverse transcription PCR revealed the existence of five alternate splice forms of CpTRPA5. Identification of a novel TRPA and its splice forms in codling moth antennae open for investigation of their possible sensory roles and implications in behavioral responses related to olfaction.